Syns vi - finns vi !? - Ek, Kristofer; Furness-Lindén, Anna (2005)
A couple of hundred years ago half of the earth's surface was covered by forest. Today, only half remains and every year an area the size of Nepal is disappearing. Deforestation, together with the burning of fossil fuels, is also one of the reasons for the increasing greenhouse effect. Another relatively unknown problem for the world's forests is the trade with illegally harvested timber. From an increasing awareness regarding problems with the forests of the world, the Forest Stewardship Council, FSC, was established. FSC is an international non-profit certification organization working for a sustainable management of the world's forests.